Relationship of Internal Locus Of Control To Career Maturity Through Self-Efficacy - Ummi Qudsiyah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This research aims to determine the relationship between internal locus of control and career maturity through student self-efficacy. The sample used was active students at Semarang State University 2017. The sampling technique in this research used a random sampling technique with degrees of error using the Isaac Michael table guide. The data analysis technique used is the template/model 4 mediation statistical analysis technique developed by Hayes. The research results show that internal locus of control through self-efficacy does not significantly affect the career maturity of students at the Faculty of Education, Semarang State University. The internal locus of the control variable, which has no significant effect on self-efficacy, can be explained by (β = 0.0937; t(321) = 0.5160; and p > 0.05).